Evaluasi Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Dana Bantuan Operasional Sekolah (BOS) di SMA PGRI PURI Kabupaten Mojokerto - Cici Larasati Herliana (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2018)
School Operational Assistance funds(BOS) is a government program that is basically provide funding for non-personnel operating costs for primary education units as implementers of compulsory education programs. The BOS program is expected to be managed according to the principles of School Based Management (SBM). Therefore, in the management of BOS funds, schools are required to develop fund management professionally, transparently and accountably The purpose of this study is to evaluate the accounting information system for BOS funds. The object of this research is Pgri Puri Senior High School. Testing is done by evaluating the accounting information system on the organizational structure, documents, internal control systems andthe reports produced. This study uses descriptive qualitative analysis method, which describes thoroughly the implementation of the accounting of the information system applied in Pgri Puri Senior High School and compared with theories related to accounting information systems, so that the desired results of this study are obtained. The results of this study indicate that the accounting information system, especially the income system, cash receipts and cash outlay, runs effectively. This can be seen from the organizational structure that is according to the characteristics of the school, sufficient and well-designed documents, an internal control system and sufficient reports,althoughthe flowchart design has not yet been established in the accounting information system.